2021
DOI: 10.1111/ggi.14290
|View full text |Cite
|
Sign up to set email alerts
|

Tooth loss, dental prostheses use and cognitive performance in older Brazilian adults: The SABE cohort study

Abstract: To investigate the within-and between-person longitudinal effects of tooth loss and the use of dentures, clinically assessed by dentists, on cognitive decline in a representative sample of community-dwelling older Brazilian adults. Methods: Data came from 1265, 1112 and 1021 individuals aged ≥60 years who participated in the second (2006), third (2010) and fourth (2015) waves, respectively, of the Health, Well-being and Aging study (SABE). Cognitive performance was evaluated with the abbreviated version of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…11 As discussed in Part I 12 there may be some association between chewing and cognition and a recent study suggested that the use of dental prostheses might be a protective factor for cognitive decline. 13 It has even been suggested that the use of RPDs may have long-term benefits in reducing mortality, although it was acknowledged that further research is necessary. 14 The majority of partially edentate people in the world will not be able to afford a fixed or implant-supported prosthesis merely because the majority of people in the current world order are poor.…”
Section: Discussion and Conclusion To The Seriesmentioning
confidence: 99%
“…11 As discussed in Part I 12 there may be some association between chewing and cognition and a recent study suggested that the use of dental prostheses might be a protective factor for cognitive decline. 13 It has even been suggested that the use of RPDs may have long-term benefits in reducing mortality, although it was acknowledged that further research is necessary. 14 The majority of partially edentate people in the world will not be able to afford a fixed or implant-supported prosthesis merely because the majority of people in the current world order are poor.…”
Section: Discussion and Conclusion To The Seriesmentioning
confidence: 99%
“…It remains unclear whether this is due to statistical power limitations, a potential longer term benefit of dentures in relation to dementia risk or other characteristics of participants with dentures not captured in this study. The role of dentures is difficult to pinpoint in this study because the presence of dentures might represent a level of motor and psychological adaptability beyond improved chewing ability, for example, facilitating healthy nutrition or even improved social and psychological health (Bof de Andrade et al, 2021; Yang et al, 2022). Jaw‐specific analyses largely corroborated with the overall tooth count findings and did not suggest jaw‐specific differences, especially after accounting for reverse causality bias.…”
Section: Discussionmentioning
confidence: 99%